2018
DOI: 10.1371/journal.pone.0209747
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of N-acetylglucosamine and hyaluronic acid combined with PLGA scaffolds for osteochondral repair in rabbits

Abstract: Repairing damaged articular cartilage is particularly challenging because of the limited ability of cartilage to perform self-repair. Intra-articular injections of N-acetylglucosamine (GlcNAc) comprise a method of repairing full-thickness articular cartilage defects in the rabbit knee joint model. To date, the effects of administration of GlcNAc and hyaluronic acid (HA) have been investigated only in the context of osteoarthritis treatment. Therefore, we evaluated the therapeutic effects of using cell-free por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…BAT is essential for animals under cold plateau conditions, which is a hot area of research on the plateau animals adapt to the cold environment in the plateau area. PPAR is a key regulator of BAT cell differentiation and heat production 32 . The PPAR signaling pathway can promote the differentiation of mesenchymal progenitor cells into BAT cells, helping to produce heat and increase energy consumption.…”
Section: Discussionmentioning
confidence: 99%
“…BAT is essential for animals under cold plateau conditions, which is a hot area of research on the plateau animals adapt to the cold environment in the plateau area. PPAR is a key regulator of BAT cell differentiation and heat production 32 . The PPAR signaling pathway can promote the differentiation of mesenchymal progenitor cells into BAT cells, helping to produce heat and increase energy consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, HA has been shown as a promising treatment modality in osteoarthritis, and osteochondral lesions of the knee by reducing VAS and increasing function in human studies [ 14 , 38 , 53 55 ]. Also, there has been evidence in animal models of higher quality hyaline cartilage being generated after osteochondral lesions when scaffolds were combined with HA [ 32 34 ], which may lead to a longer-term relief of pain and potential decrease for progression of arthritis when compared to fibrocartilage generated from traditional microfracture alone, especially in obese patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recommended improvements for future studies in this area would be the blinding of observers, and assessing patients at later follow-up periods. Longer-term follow-up is particularly important to assess the durability of HA and MF as basic science evidence has shown the potential for high-quality hyaline cartilage generation by MF coupled with HA versus the lower quality generated fibrocartilage by MF alone [ 32 34 ]. Additional examinations to assess the quality of repair tissue and regeneration of hyaline cartilage would provide more information regarding the actions of HA, alone or in combination with other biological treatments, in cartilage regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…To improve delivery and distribution, GlcNAc has been intra-articular injected in a rabbit model of OA, using cell-free porous poly lactic-co-glycolic acid (PLGA) graft implants. The results showed that the acetyl-aminosugar promoted the repair of full-thickness articular cartilage defects in the animal joints and that the effect is prolonged or increased when a combination of compounds was used [ 23 ]. Moreover, GlcNAc has been shown to exert anti-inflammatory activity and the ability, albeit of limited potency, in stimulating the synthesis of certain factors whose degradation is associated with OA.…”
Section: Introductionmentioning
confidence: 99%